Suryanamaskara and Meditation on Physical health. - Patil, Amit A; Patil, Vidula; Gound, Anjali (International Research Journal of Ayurveda & Yoga, 2024)
There are numerous health benefits of Suryanamaskar (sun salutation) for different system of the body. By practicing Suryanamaskar each and every cell of body get revitalize and regenerated, therefore it is highly recommended by all yoga experts for healthy routine life. Regular practice of Suryanamaskar gives strength, flexibility and vitality to the body. Though the Suryanamaskar steps are very scientific and practical science ancient time but still it needs advance modern scientific justification to spread it globally, keeping this in mind the present study was carried out to see the effects of suryanamaskara along with pranayama and meditation on physical health. The effect was accessed with Body Mass Index (BMI). The present article is the short communication regarding the study.